The impact of grouping in mathematics: Views from Kurdistan-Iraqi high school teachers - Alshatri, Shwan Hussein (Indonesian Journal of Science and Mathematics Education, 2024)
Mathematics is one of the primary disciplines in education that can be used to measure students' abilities in learning and understanding scientific equations. This research explores the effectiveness of grouping methods in teaching mathematics at the high school level and its impact on students' scientific literacy. Using data analysis and descriptive methods, this study gathered responses from 60 high school mathematics teachers in Kurdistan who completed questionnaires on using grouping methods in teaching. The results show that all teachers found the grouping method to be an effective way to teach mathematics, improve student understanding, and facilitate student cooperation and critical thinking. The implications of this study include providing beneficial teaching methods for teachers and new insights into the practical and theoretical literature on group learning in mathematics. This research contributes to developing more effective mathematics teaching strategies in high schools, focusing on group learning approaches.